Mining waste as heterogeneous catalysts - Kim, Soo Lim; Yang, Heejin; Lee, Seonho; Cho, Si Kyung; Lee, Chang Gu; Azat, Seitkhan; Lee, Jechan (Green Chemistry, 2025)
Mining activities generate significant waste that poses serious environmental challenges, emphasizing the urgent need for effective waste management strategies. Mining waste, such as tailings, pyritic materials, ore residues, and metallurgical by-products, is rich in metals and metal oxides (e.g., Mg, Fe, and Al species) that can serve as catalytic active sites or supports. This intrinsic property highlights its potential for application as heterogeneous catalysts. In recent years, there has been growing interest in utilizing mining waste for catalytic applications, sparking preliminary studies that explore its catalytic capacities and mechanistic roles across various processes. This review consolidates recent advancements in employing mining waste as catalysts, focusing on their characterization, preparation methods, and catalytic performance in diverse reactions. These include dry and steam reforming, wastewater treatment processes (e.g., Fenton, photo-Fenton, peroxymonosulfate activation, electrochemical methods, and ozonation), environmental remediation (e.g., denitrification, carbon monoxide oxidation, and carbon dioxide reduction), and other chemical transformations (e.g., esterification, acetylation, and hydrodeoxygenation). Furthermore, the review discusses key challenges and critical considerations for advancing research in mining waste-based catalysts.
Keywords: Catalytic active sites; Environmental challenges; Heterogeneous catalyst; Metal-oxide; Metallurgical by-products; Mining activities; Mining waste; Pyritic materials; Waste management strategies; ]+ catalyst